3D Carbon/Carbon composites for beam intercepting devices at CERN. Issue 1 (11th February 2019) - Nuiry, François‐Xavier; Calviani, Marco; Bergeret, Maxime; Pianese, Stefano; Butcher, Mark; Grec, Lucian‐Mircea; Lechner, Anton; Frankl, Matthias Immanuel; Maciariello, Fausto Lorenzo; Pichon, Thierry
Abstract: 3D Carbon/Carbon (3D CC) is a well‐known industrial composite material for high‐temperature applications. One of its main advantages resides in its ability to maintain good material characteristics at elevated temperatures (higher than 2700°C), which makes it potentially interesting for beam interaction applications where high strength at high temperature is required. The ability of beam intercepting devices to withstand direct impacts of high‐energy proton beams is essential for the operation of the Large Hadron Collider (LHC) at the European Laboratory for Particle Physics (CERN). Following successful beam impact tests at CERN, as well as positive vacuum acceptance and metrology tests, several collimators and beam extraction absorbers are currently being equipped with 3D CC composite, as part of the LHC Injector Upgrade (LIU) and High Luminosity LHC (HL‐LHC) projects.